Scanning electron microscopy of antennal sensilla of the eight Anopheles species of the Hyrcanus Group (Diptera: Culicidae) in Thailand - Chayanit Hempolchom (2018)
© 2016, Springer-Verlag Berlin Heidelberg. Antennal sensilla were first investigated in the eight medically and veterinary important Anopheles mosquito species (Anopheles argyropus, Anopheles crawfordi, Anopheles nigerrimus, Anopheles nitidus, Anopheles paraliae (= Anopheles lesteri), Anopheles peditaeniatus, Anopheles pursati, and Anopheles sinensis) of the Hyrcanus Group in Thailand, using scanning electron microscopy (SEM). Four types of sensilla, including sensilla chaetica (large and small), sensilla trichodea (sharp- and blunt-tipped), sensilla basiconica or grooved pegs (types I, II, and III), and sensilla coeloconica (large and small), were observed on the female antennae of the eight species. The greatest number of sensilla found along the flagellum of all the Anopheles species consisted of sensilla trichodea. Grooved pegs type II were not found on the antennae of An. peditaeniatus. Interestingly, clusters of 10–15 grooved pegs type III, with blunt-tipped and unevenly grooved-lengthwise sensilla, and a sunken group of 7–12 grooved pegs type III, with slightly curved and point-tipped sensilla, were found distally on flagellomeres 3–7 of An. argyropus and An. peditaeniatus, respectively. In addition, the key for species identification, based on fine structure and morphometrics of antennal sensilla among the eight species, was constructed and differentiated successfully. However, in order to focus intensively on the exact function of these sensilla, further electrophysiological study is needed in understanding their significant role in mosquito behavior, especially when these insects seek hosts for transmitting pathogens to humans.